Association of Abl interactor 2, ABI2, with platelet/lymphocyte ratio in patients with renal cell carcinoma: A pilot study - Ergun, Sercan (Int J Exp Pathol, 2020)
There are many unknown aspects of the pathogenesis of renal cell carcinoma (RCC). The aim of the current study was to define new RCC‐related genes and measure their associations with RCC and clinical parameters, especially platelet/lymphocyte ratio which may be an independent predictor of prognosis in patients with RCC and other forms of cancer. Via in silico analysis upon RCC‐specific deleted genes in chromosome 3, four possible ceRNAs (ATXN3, ABI2, GOLGB1 and SMAD2) were identified. Then, the expression levels of these genes in tumour and adjacent healthy kidney tissues of 19 RCC patients were determined by real‐time PCR. ATXN3 and GOLGB1 gene expression levels increased but ABI2 gene expression level decreased in tumour kidney tissues when compared to normal ones. ATXN3, ABI2 and GOLGB1 gene expression levels were significantly higher in Fuhrman grade 4 than other grades (P < .001). ABI2 gene expression levels were significantly associated with higher platelet/lymphocyte ratio of the patients with RCC (P < .05). ATXN3, ABI2 and GOLGB1 may predict higher RCC grades. Also, ABI2 may regulate platelet/lymphocyte ratio which may be an independent predictor of RCC and other forms of cancer.